(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The present study is related to the implementation of Electron Beam Welding of 316L stainless steel blanks obtained by traditional methods of plastic deformation and a blank made of LaserForm Maraging Steel obtained by Additive manufacturing also known as 3D Metal Printing Technology. A microstructural analysis was performed using a Scanning Electron Microscopy (SEM). To determine the chemical distribution at the fusion zone (FZ) an energy dispersive spectroscopy (EDS) was used. Vickers microhardness distribution across the welded seam was investigated in two zones – the first one at 1 mm from the surface and the second one at 3 mm from the surface.